Urea–hydrogen peroxide prompted the selective and controlled oxidation of thioglycosides into sulfoxides and sulfones - Singh, Adesh Kumar; Tiwari, Varsha; Kunj Bihari, Mishra; Gupta, Surabhi; Kandasamy, Jeyakumar (Beilstein-Institut Zur Forderung der Chemischen Wissenschaften, 2017)
A practical method for the selective and controlled oxidation of thioglycosides to corresponding glycosyl sulfoxides and sulfones is reported using urea–hydrogen peroxide (UHP). A wide range of glycosyl sulfoxides are selectively achieved using 1.5 equiv of UHP at 60 °C while corresponding sulfones are achieved using 2.5 equiv of UHP at 80 °C in acetic acid. Remarkably, oxidation susceptible olefin functional groups were found to be stable during the oxidation of sulfide.
Keywords: monosaccharides; oxidation; sulfones; sulfoxides; thioglycosides; urea–hydrogen peroxide